6-(4y-8)=3-5y

Simple and best practice solution for 6-(4y-8)=3-5y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-(4y-8)=3-5y equation:


Simplifying
6 + -1(4y + -8) = 3 + -5y

Reorder the terms:
6 + -1(-8 + 4y) = 3 + -5y
6 + (-8 * -1 + 4y * -1) = 3 + -5y
6 + (8 + -4y) = 3 + -5y

Combine like terms: 6 + 8 = 14
14 + -4y = 3 + -5y

Solving
14 + -4y = 3 + -5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '5y' to each side of the equation.
14 + -4y + 5y = 3 + -5y + 5y

Combine like terms: -4y + 5y = 1y
14 + 1y = 3 + -5y + 5y

Combine like terms: -5y + 5y = 0
14 + 1y = 3 + 0
14 + 1y = 3

Add '-14' to each side of the equation.
14 + -14 + 1y = 3 + -14

Combine like terms: 14 + -14 = 0
0 + 1y = 3 + -14
1y = 3 + -14

Combine like terms: 3 + -14 = -11
1y = -11

Divide each side by '1'.
y = -11

Simplifying
y = -11

See similar equations:

| 11x^2-24x-261=0 | | 1/5x-2=-2 | | y=1/5(-5)-2 | | 5-1=0 | | 40x+50y=249 | | -13-2y=-3 | | 2x+3x=400 | | x-2(4)=-3 | | (X-6)/(x+1)=0 | | 67+x=182.50 | | x(x-2)=124 | | (T/t-1)+(2/t+1)=(2/t^2-1) | | 3x+45=10x+24 | | (4x+37)=(3x+43) | | 25=X+7 | | 17=7+27t-16t^2 | | 2x^2-x=2-4x | | b=4a-17-26 | | 5y-7+y+57=5y+50-2y | | -6(5p+3)-44=2(2p+3) | | q=2p+8 | | -2(3x-3)+9x-4= | | -3x-5/4 | | 11(c-3)+8=7+c-32 | | 4y-6=2y+2 | | 12000(1+.082)(8)=a | | -30+4k=k-2k | | 865=36000r(10/12) | | 2x^2-10000000x-5=0 | | 2x^2-10000x-5=0 | | 2x^2-1000x-5=0 | | x^2-226x-30=0 |

Equations solver categories